Model and Properties of the Quasi-Symmetrical Helical Deflection System - Štaras, S.; Burokas, T. (Elektronika ir Elektrotechnika, 2006)
Properties of the quasi-symmetrical helical deflection system are considered. The system was developed for the super-wide-band traveling-wave tubes that can be used for measurements of momentary voltages using compensation method. The system contains two helices and shields. One helix is used as the retardation electrode of the traveling-wave deflection system. Turns of the other helix are short circuited. This helix can be used as the compensation voltage electrode. The influence of the short circuited turns on retardation factor, input impedance of the quasi-symmetrical system and attenuation of the propagating wave in the system is considered. The short circuited turns cause increase of retardation factor and input impedance of the quasi-symmetrical system in the lower frequency range. The influence of the short circuited turns on retardation factor and input impedance decreases with frequency because the electromagnetic field in the slow-wave structures has surface character and electromagnetic coupling between the helical electrode of the system and the short circuited turns of the compensation electrode decreases with frequency. Losses in the short circuited turns cause attenuation of the traveling wave. In order to reduce attenuation, it is necessary to increase conductivity of the short circuited turns and to reduce coupling between the slow-wave and compensation electrodes. Ill. 7, bibl. 9 (in Lithuanian, summaries in English, Russian and Lithuanian).